Clinical study on effect of Ketakeladi paththuwa for anatomical deformed Janu sandhigata vata: An open label, single arm clinical study - Palliyaguru, S.; Samarawickrama, A.G. (University of Colombo, 2025)
Sandhigata vata is a clinical condition; Prakupita vata affects Sandhi and causes Sandhishula, Sandhishotha, and Sandhigraha. A study was carried out open label, single arm clinical study with preand post-test design at Ayu Sri Ayurveda Hospital. The present study was designed to evaluate the effect of Ketakeladi paththuwa for anatomical deformed Janu sandhigata vata. Ethical approval was taken from ERC-23/208/FIM. Present study was conducted on 30 patients aged between 50 - 70 years, diagnosed by cardinal symptoms and X-ray findings. Intervention was done by the application of Ketakeladi paththuwa with manupulation reduction on affected Janu sandhi for a period of one month. All the patients were examined weekly based on gradings given for signs and symptoms. Assessment was done by considering changes in the subjective and objective parameters before and after treatment. In this study 44.89% were in 50 - 60-year age group. According to sex 59.18% were female patients. Improvement of walking time was 61.15%, improvement of climbing time was 68.88%, left knee joint flexion (Sandhigraha) percentage of relief was 65.31%, while in right knee joint flexion it was 57.42%. Out of 30 patients, 9 (30%) got complete remission, 12 (40%) got marked improvement, and 8 (26.67%) got mild improvement and one patient remained unimproved. These results were statistically significant at the level of P<0.001. Therefore, manipulation reduction with applying Ketakeladi paththuwa attributed to the regenerative action of Janu sandhi.
Keywords: Ketakeladi paththuwa; Janu sandhigata vata; Sandhishula; Sandhishotha